Insights into the Functions of a Prophage Recombination Directionality Factor - Mireille Ansaldi; Vincent Méjean; Gaël Panis; Nathalie Franche (Viruses, 2012)
Recombination directionality factors (RDFs), or excisionases, are essential players of prophage excisive recombination. Despite the essentially catalytic role of the integrase in both integrative and excisive recombination, RDFs are required to direct the reaction towards excision and to prevent re-integration of the prophage genome when entering a lytic cycle. KplE1, HK620 and numerous (pro)phages that integrate at the same site in enterobacteria genomes (such as the argW tRNA gene) all share a highly conserved recombination module. This module comprises the attL and attR recombination sites and the RDF and integrase genes. The KplE1 RDF was named TorI after its initial identification as a negative regulator of the tor operon. However, it was characterized as an essential factor of excisive recombination. In this study, we designed an extensive random mutagenesis protocol of the torI gene and identified key residues involved in both functions of the TorI protein. We show that, in addition to TorI-TorR protein-protein interaction, TorI interacts in solution with the IntS integrase. Moreover, in vitro, TorR and IntS appear to compete for TorI binding. Finally, our mutagenesis results suggest that the C-terminal part of the TorI protein is dedicated to protein-protein interactions with both proteins TorR and IntS.